Epidemiology of athletic injuries - McKeag, D. B.; Hough, D. O.
For our purposes in athletic medicine, epidemiological data can be used to: · Identify causes of injuries. · Provide a more accurate picture of clinical reality. Clusters of injuries (and the resulting media attention they often generate) give a distorted view of reality; on the other hand, data may reveal a previously unsuspected injury problem. · Determine the effectiveness of preventive measures (on a local or national scale), whether they are rule changes, new or modified equipment, or modifications of training techniques. · Monitor the health of athletes, which will assist in rational medical planning. · Quantify the risks of various types, frequencies, and intensities of exercise activities. · Provide an overview of long-term injury trends in specific sports.